Effect of list length on recall after dichotomous visual presentation. - Martin, M (1980)
A visual analogue of an auditory dichotic listening experiment was carried out using what may be termed dichotomous visual presentation of lists of either three or four stimuli. Each stimulus consisted of several identical letters which were arranged so as to form the outline of a second, large letter. Subjects attended to either the small or large letters, and recalled either the attended or unattended letters first. It was found that the results for the three-stimulus and four-stimulus lists differed substantially; they were interpreted as consistent with the model of short-term memory proposed by Broadbent (1975). © 1980.